Prevalence of fetal and neonatal mortality due to congenital anomalies in the state of Maranhão, Brazil, from 2001–2016 - Reis, Luzivan Costa; Kaizer, Wesley Luciano; Schüler-Faccini, Lavínia (Clinical and Biomedical Research, 2021)
Introduction: The infant mortality rate (IMR) is an important health indicator directly associated with living conditions, prenatal care coverage, social development conditions, and parental education, among others. Worldwide, the infant mortality rate was 29/1000 live births in 2017. Therefore, this study aimed to evaluate the fetal and infant mortality rates due to congenital anomalies (CA) in Maranhão from 2001 to 2016. Methods: Data were obtained from the SINASC, and SIM databases. We used simple linear regression, Poisson distribution, and ANOVA (Bonferroni’s post hoc test). We analyzed the public data (2001–2016) of 1934858 births and determined the fetal, neonatal, perinatal, and post-neonatal mortality rates associated with CA by mesoregions. Results: The IMR in Maranhão was 17.01/1000 live births (95%CI, 13.30-20.72) and CA was the cause of death in 13.3% of these deaths. Mortality due to CA (per 1000 live births) was 0.76 (95%CI, 0.74–0.85) for fetal mortality rate and 2.27 (95%CI, 1.45-3.10) for infant mortality rate. Geographic and temporal variations were observed with a slight increase in recent years for deaths attributable to CA, and in the northern part of Maranhão. Conclusions: Mortality rates due to CA in Maranhão increased over the period 2001–2016 possibly as a result of improved maternal-infant health conditions eliminating other causes of death. Therefore, efforts to improve early diagnosis and better treatment of congenital anomalies should be considered to reduce its impact on child mortality.